METABOLIC COMPLICATIONS OF GROWTH HORMONE DEFICIENCY IN PATIENTS WITH ISCHEMIC HEART DISEASE (American Journal of Interdisciplinary Research and Development, 2024)
In this article, the authors discussed the results of investigation of 21 adults with ischemic heart disease (IHD) and metabolic syndrome with growth hormone deficiency syndrome in adults (GHD). The investigation of hormonal status disorders found of the level of STH and IGF-1 in blood plasma. It was established that frequency of GHD in patients with IHD of both groups was 15 cases from 21 patients (71.4%). Besides that, 8 patients from 15 (53.3%) with GHD have low levels of GF-1 too. The levels of STH was in range from 0.15 ng/ml to 0.53 ng/ml in 13 (86.6%) patients from 15, which noted the high frequency of low levels of STH in both groups. And the levels of IGF-1 - in range rom 58 ng/ml to 120 ng/ml in 10 (50%) from 20 patients.